INITIATIVES FOR THE SAFETY OF PEDESTRIANS IN ASIAN COUNTRIES: A SYSTEMATIC LITERATURE REVIEW - Nazneen, Numera; Zainol, Rosilawati (Journal of Surveying, Construction and Property, 2021)
Walking is a standard communication mode around the world. Despite its’ importance, walking facilities are less prioritized, and pedestrians are often prone to many accidents, which denotes the essence of pedestrians’ safety. To date, very few studies focus on comparing safety initiatives in different countries. This literature review aims at presenting the initiatives taken for pedestrians’ safety, specifically in Asian countries, where the pedestrian death rate is on the rise. With the keywords (initiatives, safety, pedestrians), databases (WoS, Scopus, Science Direct), eligibility and exclusion criteria for the systematic literature review, 20 articles are selected using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. From the extracted data, initiatives taken for the safety of pedestrians are divided into two themes and eight sub-themes: for Specific Area (5 sub-themes) and Parts of Roadways (3 sub-themes). The result shows that most of the safety initiatives focused on different sections of roadways compared to the needs of areas specified for the respective affairs of a group of people. Also, regarding studies on safety initiatives, there is an insufficient exploration of safety measures for pedestrians by researchers. Thus, this study gives an idea of the initiatives prevailing for pedestrians’ safety and the aspects that require special attention from the related authorities of different Asian countries. Researchers are recommended to conduct future research on sidewalk safety, adapt qualitative study and PRISMA method for improved systematic review reporting.